Seri-Technics: Historical Silk Technologies - Giorgio Riello (Studies 13: Max Planck Research Library for the History and Development of Knowledge, 2020)
At a time when the social and cultural importance of silk in the pre-modern global world is increasingly evident, this volume returns to the issue of technology and queries the ways in which actors determined the nature of silk by deploying, selecting, or pursuing certain set of technics, practices, or ideals (while dismissing or ignoring others). Drawing on the growing research on silk's cultural, social, economic, and intellectual implications, these chapters provide a fresh look at how technical processes have been historically shaped to define the identity of silk. Calling the technical system that has generated ideas about silk a form of textile seri-technics, this volume presents historical case studies that, sampled from diverse cultural regions, exemplify major technological processes and practices of silk textile production. The contributions tackle five technical attributes and principles of action that have come to make- up historical seri-technics.